Assessing the cost feasibility of solar projects in Canada using the RETScreen Expert software - Apeksha (2021)
The climate emergency is melting glaciers, destroying forests and increasing sea water levels worldwide. The burning of fossil fuels, current urbanization and transportation patterns, careless industrialization all release harmful greenhouse (GHG) gases to the atmosphere leading to the biggest issue faced by humanity: climate change. Countries around the world are addressing GHG emissions by transitioning to renewable energy sources. Energy experts calculate that offsetting 50% of all future demand growth in thermal electricity generation by solar photovoltaics (PVs) would reduce annual global carbon dioxide emissions by 10% in 20 years and 32% in 50 years. Installing more renewable energy projects worldwide to reduce GHG emissions is a way forward to avert the climate emergency. Countries like China, India and Germany on the one hand are the top greenhouse gas emitting countries in the world and on the other are becoming world leaders in installing solar projects, thereby reducing global installation costs and making solar power more financially and technically viable. By investing in research, development, and deployment those three countries are making solar PV systems better and extremely cost-effective for every other country. Empirical data clearly shows that today solar PV is now the cheapest source of electricity in the world and has reached grid parity in comparison to fossil fuel sources. Canada is amongst the top 10 countries in the world in terms of generating the most greenhouse gas emissions. In 2019, Canada emitted more than 1,982 MTCO2 emissions on this earth and is ranked eighth in the world in terms of emissions. As per the Paris Agreement, 2015, Canada had committed to reduce its GHG emissions by 30 per cent from 2005 levels by 2030. To achieve that ambitious goal, Canada needs to focus on policies and processes that would help reduce GHG emissions in the long run. But is Canada making sufficient efforts to reach their target and to change the policies that favor more renewable energy ...